2006
DOI: 10.1007/s10750-006-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term decompositional state does not influence use of wood by macroinvertebrates in subtropical, coastal plain streams

Abstract: Woody debris is an important habitat component, particularly in streams that lack other hard substrates. Research suggests a general relationship between increasing invertebrate density, diversity, and taxa richness with increasing wood decay in lotic systems, with some authors observing invertebrate taxonomic succession as decay proceeds. We designed a field experiment using colonization of known-aged woody debris in two streams to examine patterns in invertebrate colonization, density, diversity, richness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Despite forming b20% of the area colonizable by macroinvertebrates in Congaree's Cedar Creek, instream wood has N90% of the standing crop at a given time, as well as the highest species richness and density of available substrates (Smock and Gilinsky, 1982). Studies of other bottomland hardwood wetlands and blackwater rivers also indicate that instream and floodplain wood is a hot spot for invertebrate richness and arthropod biomass (Benke, 2001;Braccia and Batzer, 2001), although macroinvertebrate abundance and diversity are also influenced by the location of the wood (swamp versus tributary and outflow stream sites; Thorp et al, 1985) and potentially by the degree to which the wood is decayed (Kaller and Kelso, 2006). Submerged wood is especially important in sand-bed streams, where it provides stable attachment points for filter-feeding macroinvertebrates (Benke, 1998).…”
Section: Lynches2-floodplainmentioning
confidence: 99%
“…Despite forming b20% of the area colonizable by macroinvertebrates in Congaree's Cedar Creek, instream wood has N90% of the standing crop at a given time, as well as the highest species richness and density of available substrates (Smock and Gilinsky, 1982). Studies of other bottomland hardwood wetlands and blackwater rivers also indicate that instream and floodplain wood is a hot spot for invertebrate richness and arthropod biomass (Benke, 2001;Braccia and Batzer, 2001), although macroinvertebrate abundance and diversity are also influenced by the location of the wood (swamp versus tributary and outflow stream sites; Thorp et al, 1985) and potentially by the degree to which the wood is decayed (Kaller and Kelso, 2006). Submerged wood is especially important in sand-bed streams, where it provides stable attachment points for filter-feeding macroinvertebrates (Benke, 1998).…”
Section: Lynches2-floodplainmentioning
confidence: 99%
“…In this way, decaying wood is a perfect habitat to opportunist worms as capitellids and oligochaetes (Rizzo & Amaral, 2001;Dean, 2001b). Kaller and Kelso (2006) found that insects and molluscs are the main components in decaying woods, of coastal freshwater streams, in South-Western Louisiana. The adaptations of these groups to wood boring may have allowed them to dominate the decaying wood in low salinity regimes.…”
Section: Polychaetesmentioning
confidence: 99%
“…For instance, invertebrate richness may increase with decay (Braccia andBatzer 2001, Ballinger et al 2010), and density may vary (Collier and Halliday 2000) or be unrelated to decay (Braccia and Batzer 2001). Based on some of these studies and on their own findings, Kaller and Kelso (2006) stressed the difficulty of making generalizations about the effect of decay on macroinvertebrates. We think that part of the difficulty arises from limited tracking of crucial features in the decay of sampled wood, such as decay time, age, size, species, and waterlogging period.…”
Section: Taxon Responsesmentioning
confidence: 99%
“…In contrast, Pitt and Batzer (2011) found that conditioning had minimal influence on how wood was used by macroinvertebrates in streams in the southeastern USA. Kaller and Kelso (2006) suggested that stream invertebrates readily used all incoming wood regardless of its condition, and they invoked opportunistic colonization as the primary mechanism explaining similar assemblages on wood with various conditioning. In disentangling this contradiction between our results and those reported by others, we first note that our systems differ markedly from those where most other related work has been conducted.…”
Section: Trait Responsesmentioning
confidence: 99%
See 1 more Smart Citation